Ancaman Limbah Pertanian Terhadap Air Tanah: Kajian Komprehensif dan Strategi Mitigasi - Maulidya, Annisa; Ihsan, Taufiq (Universitas Tanjungpura, 2025)
This review aims to assess the diversified risks associated with agricultural pollution of groundwater and to propose effective mitigation measures. In that direction, the article discusses the source and pathways of agricultural contaminants, underlining the controlling role of geology in contaminant transport. In this paper, an attempt will be made to assess critically the adverse effects of such contaminants on human health, the environment, and the economy. This requires interdisciplinary approaches to risk assessment and management that involve geologists, hydrologists, agronomists, environmental scientists, policymakers, and farmers. This review, therefore, summarizes good management practices